Dosing of Electrical Parameters in Deep Brain Stimulation (DBS) for Intractable Depression: A Review of Clinical Studies - Ramasubbu, Rajamannar; Lang, Stefan; Kiss, Zelma H. T. (Frontiers in Psychiatry, 2018)
Abstract Background: The electrical parameters used for deep brain stimulation (DBS) in movement disorders have been relatively well studied, however for the newer indications of DBS for psychiatric indications these are less clear. Based on the movement disorder literature, use of the correct stimulation parameters should be crucial for clinical outcomes. This review examines the stimulation parameters used in DBS studies for treatment resistant depression (TRD) and their relevance to clinical outcome and brain targets. Methods: We examined the published studies on DBS for TRD archived in major databases. Data on stimulus parameters (frequency, pulse width, amplitude), stimulation mode, brain target, efficacy, safety, and duration of follow up were extracted from 29 observational studies including case reports of patients with treatment resistant unipolar, bipolar and co-morbid depression. Results: The algorithms commonly used to optimize efficacy were increasing amplitude followed by changing the electric contacts or increasing pulse width. High frequency stimulation (> 100Hz) was applied in most cases across brain targets. Keeping the high frequency stimulation constant, three different combinations of parameters were mainly used: (i) short pulse width (60-90 us) and low amplitude (0-4V), (ii) short pulse width and high amplitude (5-10 V), iii) long pulse width (120-450 us) and low amplitude. There were individual variations in clinical response to electrical dosing and also in the time of clinical recovery. There was no significant difference in mean stimulation parameters between responders and non-responders suggesting a role for stimulation unrelated factors in response. Conclusions: Although limited by open trials and small sample size, three optimal stimulation parameter combinations emerged from this review. Studies are needed to assess the comparative efficacy and safety of these combinations, such as a registry of data from patients undergoing DBS for TRD with individual data on stimulation parameters.